O (re) conhecimento sociolingüístico na escola : sua implicação para o ensino - Martins, Alessandra Avila (2005)
This paper is a research with the aim to present the socio-linguistic reality expressed in written texts of students that have been approved or that have been flunked in the 5th and 6th years of Elementary School and that are from an institution of public teaching in the city of Erechim, in the North of Rio Grande do Sul. Data analysis reveals the importance of the socio-linguistic knowledge and acknowledgement of the students so that they are not punished by the system of evaluation. In this paper, we found support in the Socio-linguistic and in topics related to the area of education to discuss the conflicting relation between the standardized written Portuguese, which the schools are always looking for, and the colloquial written Portuguese used in the context of a school that is located in the peripheral area of the city